Study of effects of fuel injection pressure on performance for diesel engine - Ahmad Muizz, Ishak (2012)
Diesel engines are used mainly in heavy duty machines and vehicles. Diesel engines have many advantages such as high fuel efficiency, reliability and durability. The performance of diesel engines depends on many parameters. One of the important parameters which influence the performance of diesel engines is fuel injection pressure. Fuel injection pressure plays an important aspect of power performance of the engine to obtain combustion treatment. The objective of this project is to study the effects of fuel injection pressure on the performance for diesel engine. Mathematical formulation for fuel injection system developed to obtain the result to analyse the performance of diesel engine based on fuel injection pressure. The results by using simulation are shown in Chapter 4 from Figure 4.1 to Figure 4.6 and it can be concluded that the simulation results can be used to predict and study the effect of fuel injection pressure on performance for diesel engine.